Efficacy and safety of Chinese herbal medicine Wenxin Keli for ventricular premature be ats: A systematic review. (December 2016) - He, Mei; Lv, Zhan; Yang, Zheng-Wei; Huang, Jiu-Ling; Liu, Fu
Highlights: Wenxin Keli might be beneficial to reduce ventricular premature beats' numbers and relieve symptoms. Patients with numbers <360 beats/hour or with coronary heart disease may benefit the most of the Wenxin Keli. Wenxin Keli, compared with Western medicine, might be associated with a reduced risk of proarrhythmic reactions. Abstract: Background: To evaluate the efficacy and safety of the Chinese herbal extract Wenxin Keli, alone or in combination with Western medicine, for ventricular premature beats. Methods: This systematic review was registered at PROSPERO (registration number CRD42013003200). A systematic literature search of 8 core electronic databases and 3 clinical trial registries in Chinese and English, yielded 10 trials whose randomness verified by contacting the authors. The included trials were assessed by the Cochrane risk of bias tool. Results: Wenxin Keli might be more efficacious than placebo (Change of VPBs numbers, RR, 1.61, 95%CI, 1.48–1.76, P < 0.00001, I 2  = 0%;VPBs- related symptom, RR, 2.10, 95%CI, 1.91–2.30, P < 0.00001, I 2  = 0%), and the dual therapy of Wenxin Keli plus amiodarone might also be more effective than the monotherapy of amiodarone (Change of VPBs numbers, RR, 1.23, 95%CI, 1.10–1.39, P = 0.0005, I 2  = 0%; VPBs- related symptom, RR, 1.51., 95%CI, 1.30–1.76, P < 0.00001, I 2  = 0%), whereas Wenxin Keli might be comparable to metoprolol, propafenone or mexiletine (Change of VPBs numbers: metoprolol, RR, 1.01, 95%CI, 0.91–1.11, P = 0.88, I 2  = 0%; propafenone, RR, 1.05, 95%CI, 0.93–1.19, P = 0.44, I 2  = 0%; mexiletine, RR, 1.06, 95%CI, 0.96–1.17, P = 0.28. VPBs- related symptom: metoprolol, RR, 0.95, 95%CI, 0.87–1.04, P = 0.27, I 2  = 0%, propafenone. RR, 1.10, 95%CI, 0.93–1.30, P = 0.29, I 2  = 29%, mexiletine, RR, 0.94, 95%CI, 0.78–1.12, P = 0.47). Participants with ventricular premature beats' numbers < 360 beats/h or with coronary heart disease benefited the most of the Wenxin Keli therapy (Change of VPBs numbers:RR, 1.10, 95%CI, 1.02–1.20, P = 0.02, I 2  = 44%; RR, 1.71, 95%CI, 1.18–2.49, P = 0.005, I 2  = 54%, respectively). The safety analysis revealed that Wenxin Keli did not statistically significant differed from the Western medicine in respect of the incidence of total adverse drug reactions (RR, 0.59, 95%CI, 0.35–1.01, P = 0.05, I 2  = 0%), but Wenxin Keli might be associated with a reduced risk of proarrhythmic reactions (P = 0.007). The quality of the methodology of included trials was generally low. Several limitations existed that affected the validity of the findings, including the small sample size, insufficient randomization methods, poorly defined eligibility criteria, short duration of follow-up, absence of hard endpoints, and high risk of publication bias(P = 0.013). Conclusions: Wenxin Keli might be a promising alternative and complementary medicine for ventricular premature beats.